2017
DOI: 10.1371/journal.pone.0177126
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of patients with de novo versus nevus-associated melanoma in Taiwan

Abstract: Studies surveying melanomas associated with melanocytic nevi in Asia are rare. In this study, we examined whether nevus-associated melanomas differ from de novo melanomas in terms of their associations with clinical factors, histologic characteristics, and patient survival in Taiwan. Using data on cancer cases obtained from the Department of Pathology archives and the Cancer Registry of National Taiwan University Hospital, we conducted a retrospective analysis of 103 consecutive melanoma patients who were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…The results of this study show that the most frequent histological subtype corresponds to lentiginous acral melanoma (41.8 %), congruent with that reported by the INC for Colombia 16 , De Vries et al 24 in 2017 for Cali and Sheen et al in 2017 for Asian populations 28 . In contrast, in Caucasian populations there seems to be higher frequency of the superficial spreading melanoma 17 subtype (63.2 %), followed by the nodular subtype (50.4 %) 16,24,28,29 . Differences between frequencies of melanoma subtypes in Colombia, with respect to Caucasian populations, can be attributed to the ethnic origin of each population and miscegenation.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study show that the most frequent histological subtype corresponds to lentiginous acral melanoma (41.8 %), congruent with that reported by the INC for Colombia 16 , De Vries et al 24 in 2017 for Cali and Sheen et al in 2017 for Asian populations 28 . In contrast, in Caucasian populations there seems to be higher frequency of the superficial spreading melanoma 17 subtype (63.2 %), followed by the nodular subtype (50.4 %) 16,24,28,29 . Differences between frequencies of melanoma subtypes in Colombia, with respect to Caucasian populations, can be attributed to the ethnic origin of each population and miscegenation.…”
Section: Discussionsupporting
confidence: 90%
“…NAM usually appears in younger patients than de novo melanoma (DNM), with multiple nevi and in intermittently sun‐exposed skin areas as the trunk or extremities, as it occurs in our work. According to some authors, personal history of NAM is the most important risk factor to have another NAM, so this group of patients may benefit even more of digital dermoscopic follow‐up.…”
Section: Discussionsupporting
confidence: 53%
“…Sheen et al . 's retrospective study demonstrated improved recurrence‐free survival among patients with naevus‐associated compared with de novo melanomas; however, the study's predominant melanoma subtype was acral lentiginous melanoma (70.9%), limiting generalisability of the results …”
Section: Patient Demographics and Tumour Characteristics Of Naevus‐asmentioning
confidence: 88%
“…The studies that have compared survival outcomes between naevus-associated and de novo melanomas have produced conflicting results. [3][4][5][6] Superficial spreading melanoma (SSM) and nodular melanoma (NM) together account for approximately 70% of all invasive melanomas and represent the most common radial and vertical growth phase melanoma subtypes. Therefore, the aim of this study was to determine the prognosis of naevus-associated and de novo melanoma in these two melanoma subtypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation